Pengaruh Model Role Playing Terhadap Keterampilan Berpuisi Siswa Kelas III SD Laudato Si - Susana Ginting; Rani Adillah; Elly Prihasti Wuriyani; Wisman Hadi (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2024)
Based on the results of field studies conducted by researchers, the speaking skills of class III students at Laudato Si Elementary School are still less active in terms of poetry, most of them are passive during class, do not want to ask questions, remain silent when the teacher asks to speak, students still stammer, are shy and hesitant. hesitant. By understanding this, it is known that class III students still do not have poetry skills and find it difficult to communicate the information they have obtained. This research aims to find out how role playing models influence the poetry skills of class III students and to find out students' attitudes by applying role playing models to their poetry skills. The method used in this research was a quasi-experimental type of quantitative research conducted on 42 students in class III of Laudato Si Elementary School, consisting of 21 students in class III A and 21 students in class III B. This research uses Nonequivalent Control Group Design. Research results data were obtained from interviews, tests, questionnaires, observation and documentation. The mean posttest score for the control class with conventional learning had a mean of 74.90, while for the experimental class with the role playing model the mean was 80.19 and it was concluded that learning using the role playing model could help students' poetry skills.